2005
DOI: 10.1039/b416565a
|View full text |Cite
|
Sign up to set email alerts
|

Preferential CO oxidation promoted by the presence of H2over K–Pt/Al2O3

Abstract: In preferential CO oxidation in H2-rich gas, K-Pt/Al2O3(K/Pt = 10) was very effective in decreasing CO concentration below 10 ppm in the 375-410 K range, and the turnover frequency of the K-Pt/Al2O3 was 20 times as high as that of Pt/Al2O3 at 353 K; furthermore, the activity of CO oxidation was promoted drastically by the presence of H2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 15 publications
(10 reference statements)
2
55
0
Order By: Relevance
“…Although a number of catalysts more active for the PROX than the H 2 oxidation reaction have been reported [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], CuOCeO 2 and supported Pt-based catalysts appear to be most promising [2,3]. The monometallic Pt catalyst usually showed noticeable activities only above 423 K [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of catalysts more active for the PROX than the H 2 oxidation reaction have been reported [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], CuOCeO 2 and supported Pt-based catalysts appear to be most promising [2,3]. The monometallic Pt catalyst usually showed noticeable activities only above 423 K [6].…”
Section: Introductionmentioning
confidence: 99%
“…The pretreatment of Pt catalyst with water vapor was reported to enhance low-temperature catalytic activities for the PROX by increasing Pt dispersion [7]. Several groups have reported that the PROX at low temperatures could be enhanced by the addition of 2nd metals such as Ce [8], Fe [9][10][11][12], Co [13][14][15][16], Ni [13], Mn [13], and alkali metals [17][18][19]. Even though each catalyst has proved its superiority by comparison with Pt catalyst, it is difficult to assess each catalyst because different reaction conditions have been adopted.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that when the atomic ratio of K/Pt = 10/1, the K−Pt/Al 2 O 3 was 20 times as active as that of Pt/Al 2 O 3 for the PROX reaction at 80°C and was able to decrease the CO concentration below 10 ppm in the range of 100−140°C. 158 Interestingly, it seems that the promotional effect of K is more pronounced on the inert-oxidesupported Pt catalysts than that on the reducible-oxidesupported ones. Tanaka et al 162 observed that K−Pt/Al 2 O 3 and K−Pt/SiO 2 exhibited a much higher CO conversion and CO 2 (Figure 3a).…”
Section: Promoted Pgm Catalysts For the Proxmentioning
confidence: 99%
“…Another way is to directly weaken the interaction between Pt and CO by the addition of alkali base metal species. [65][66][67] However, it is difficult to control the state and interaction of the components, while the improvement in catalytic performance is also limited. 25 Very recently, a Ru-Pt core-shell (Ru@Pt) structure has been designed.…”
Section: 61mentioning
confidence: 99%